2015
DOI: 10.15405/ejsbs.168
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Anxiety to Perform Social Skill on The Relationship Between Inter-Parental Conflict and Adolescents’ Self-Efficacy

Abstract: Despite of importance of self-efficacy in psychological and social well being among adolescent, still numbers of student suffers of low self-efficacy and consequently low academic performance. Therefore, this is important to examine what factors associate with self-efficacy among adolescent. This study aims to determine the relationships between inter-parental conflict, anxiety to perform social skill and self-efficacy among late adolescent students in Hamadan University of Medical Sciences, Iran. This quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Considering that education is convertible into economic and social capital through the acquisition of jobs with good social status. Educated people can become models for the society in the future [35]. Therefore, the higher the attitude of these individuals toward organ donation, the higher effect on the improvement of the community’s attitude toward organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that education is convertible into economic and social capital through the acquisition of jobs with good social status. Educated people can become models for the society in the future [35]. Therefore, the higher the attitude of these individuals toward organ donation, the higher effect on the improvement of the community’s attitude toward organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…The total score and factors´ scores are scored separately for distress and performance. A lower score in distress and a higher score in performance represents more assertive behavior and more adaptive social skills ( Parsa et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The items fall under four factors – Negative Assertion, Positive Assertion, Initiating Assertiveness, and Expression of and Dealing with Personal Limitations. There are multiple translations of the original SIB, including French ( Bouvard et al, 1999 ), English ( Bridges et al, 1991 ; Gilbert and Allan, 1994 ), Spanish ( Arrindell et al, 1997 ), Turkish ( Eskin, 1993a , 1996 , 2003 ), Swedish ( Eskin, 1993b , 1996 , 2003 ), Persian ( Parsa et al, 2015 ), and Taiwanese ( Bridges and Arrindell, 2002 ). The SIB has good internal consistency, obtained from eight independent samples (0.75–0.97).…”
Section: Introductionmentioning
confidence: 99%
“…Depression felt by the mother and father during the postpartum period effects the interactions between the infant and parents [20]. It has been reported that low parental attachment to a child, even during childhood and adolescence periods, is associated with decreased self-efficacy and the self-esteem of the child [21,22].…”
Section: Introductionmentioning
confidence: 99%